Peran TBM Lentera Pustaka: Gerakan Literasi dan Pemberdayaan Sosial Sukaluyu - Azzahra, Ratu Nur Aisyah; Restuwulan, Tamara Aulia Restuwulan; Chaniago, Sam Mukhtar Chaniago (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
Taman Bacaan Masyarakat (TBM) Lentera Pustaka in Sukaluyu Village is a community-based literacy initiative that implements the TaBa (Reading Garden) and KePra (Illiteracy Eradication Class) programs. This study aims to examine the role of TBM in enhancing literacy and fostering social empowerment within the community. Employing a qualitative approach and a case study method, with the researcher acting as an observer, this research explores the impact of TBM’s programs. The findings indicate that TBM Lentera Pustaka significantly contributes to increasing reading interest, broadening knowledge, and developing character, particularly among children and adults. The success of these programs is supported by interactive learning methods, the active participation of volunteers, and growing community engagement. These findings affirm that community-based literacy movements can serve as effective instruments for social empowerment, fostering positive transformation at the grassroots level.